Transcriptional regulation of type I interferon responses of myeloid antigen presenting cells - Sin, Wei Xiang (2016)
Macrophages, as crucial mediators of an innate immune response, exhibit functional plasticity by playing an essential role in both the initiation and resolution of inflammation. Production of the pro-inflammatory cytokine IL-1β, via caspase-11 activation during Gram-negative bacterial infections, and of the pro-regulatory cytokine IL-10, are dependent on signaling by the pleiotropic type I interferon (IFN), IFN-β. The transcription factor IRF7 is thought to be primarily involved in the regulation of type I IFN responses in viral infections. Here we show IRF7 also regulates IFN-β responses to bacterial lipopolysaccharide in bone marrow-derived macrophages (BMDMs) but not in bone marrow-derived dendritic cells (BMDCs). In BMDMs, IRF7 co-operated with IRF3 to elicit robust IFN-β responses to endotoxin exposure, whereas BMDCs depended on IRF3 alone to mediate this response and thus displayed blunted IFN-β expression. IRF7-mediated IFN-β production is necessary for efficient expression of pro-caspase-11 in BMDMs. Accordingly, Irf7–/– mice exhibited substantially reduced serum levels of type I IFN and IL-1β, and were resistant to lethal endotoxin shock. We found that, unlike BMDCs, BMDMs constitutively expressed IRF7 protein. The high basal IRF7 expression in steady-state BMDMs was maintained by constitutive IFN-β signaling, which was in turn dependent on tonic signaling by IL-27p28. Accordingly, in response to TLR4 ligation, BMDMs but not BMDCs depended on IL-27p28 to induce IFN-β synthesis. IL-27p28-mediated IFN-β production, and not IL-27 cytokine itself, is required to restrain inflammatory responses to endotoxin exposure, since BMDMs deficient in IL-27p28 displayed reduced IL-10 synthesis and impaired STAT3-mediated anti-inflammatory responses, which were reversed by addition of exogenous IFN-β. Our data identified a tonic IL-27p28-IFN-β signaling axis as a novel cell type-specific regulator of TLR4-mediated IFN-β induction through the regulation of constitutively expressed IRF7.